Logarithmic mean Divisia index (LMDI) decomposition of coal consumption in China based on the energy allocation diagram of coal flows. (1st June 2015) - Chong, ChinHao; Ma, Linwei; Li, Zheng; Ni, Weidou; Song, Shizhong
Abstract: This manuscript attempted to analyze the influencing factors of coal consumption growth in China using the logarithmic mean Divisia index (LMDI) decomposition method developed based on the physical processes of coal utilization from raw coal to the end-use sectors. By mapping the energy allocation diagram of coal flows, we built a method to balance the energy allocation of coal flows and derived several technical influencing factors. These factors were used to develop an LMDI decomposition method suitable for analyzing the coal consumption growth of complex coal-use systems, such as that of China. The method is subsequently applied to analyze the influencing factors of China's coal consumption growth from 2001 to 2011. The results indicate the rapid growth of GDP (gross domestic production) per capita, which heavily relied on the expansion of heavy industry as the dominant factor driving coal consumption growth. Improvement in the energy efficiency of coal power generation and coal end-use combustion were the primary factors reducing coal consumption. Highlights: Energy allocation diagrams of China's coal flows from primary energy to end-use. An LMDI method for analyzing influencing factors of coal consumption growth. Policy implications for controlling the coal consumption growth in China.